1997
DOI: 10.1007/pl00006124
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Mutation and RNA Recombination to the Evolution of a Plant Pathogenic RNA

Abstract: The nucleotide sequence of 17 variants of the satellite RNA of cucumber mosaic virus (CMV-satRNA) isolated from field-infected tomato plants in the springs of 1989, 1990, and 1991 was determined. The sequence of each of the 17 satRNAs was unique and was between 334 and 340 nucleotides in length; 57 positions were polymorphic. There was much genetic divergence, ranging from 0.006 to 0.141 nucleotide substitutions per site for pairwise comparisons, and averaging 0.074 for any pair. When the polymorphic positions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 37 publications
0
26
0
2
Order By: Relevance
“…Thus, the absence of detectable recombinants in our study may also be explained by two alternative scenarios: either (i) recombination events occurred between two closely related isolates and are difficult to detect by the methods we used here or (ii) recombination events did occur, but the resulting recombinants were not favored and subsequently were selected out. Indeed, recombination events in the CMV genome and CMV satellite RNA have been described recently in both experimental systems and natural populations (1,2,4,10,16,18,37). Estimation of various population genetics parameters showed that coding regions on RNA2 (2a and 2b) were more variable, suggesting that the resultant proteins were more tolerant to amino acid changes than were regions on RNA1 (1a) and RNA3 (MP and CP) ( Table 4).…”
Section: Vol 78 2004 Population Genetics Of Cucumber Mosaic Virus 6673mentioning
confidence: 85%
“…Thus, the absence of detectable recombinants in our study may also be explained by two alternative scenarios: either (i) recombination events occurred between two closely related isolates and are difficult to detect by the methods we used here or (ii) recombination events did occur, but the resulting recombinants were not favored and subsequently were selected out. Indeed, recombination events in the CMV genome and CMV satellite RNA have been described recently in both experimental systems and natural populations (1,2,4,10,16,18,37). Estimation of various population genetics parameters showed that coding regions on RNA2 (2a and 2b) were more variable, suggesting that the resultant proteins were more tolerant to amino acid changes than were regions on RNA1 (1a) and RNA3 (MP and CP) ( Table 4).…”
Section: Vol 78 2004 Population Genetics Of Cucumber Mosaic Virus 6673mentioning
confidence: 85%
“…Proportionally, the amount of genetic variability produced after a single recombination event is larger than that produced by single point mutations. Although the importance of recombination was underappreciated in early studies of virus genome evolution, it is now recognized as a widespread phenomenon among positive-strand RNA viruses in animals (Grassly & Holmes, 1997;Holmes et al, 1999;Wilson et al, 1988) and plants (Nagy & Bujarski, 1993;Revers et al, 1996;Aranda et al, 1997;Olsthoorn et al, 2002;Bousalem et al, 2003;Cheng & Nagy, 2003;Moreno et al, 2004;Tan et al, 2004;Bonnet et al, 2005;Urbanowicz et al, 2005;Chare & Holmes, 2006;Weng et al, 2007), as well as in retroviruses such as human immunodeficiency virus type 1 Prljic et al, 2004;Althaus & Bonhoeffer, 2005;Galetto & Negroni, 2005), although it is a rare or even non-existent phenomenon among negativestrand viruses (Chare et al, 2003). There are several mechanisms by which RNA recombination may take place, the most common of which is homologous recombination (Lai, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…RNA recombination plays a major role during the evolution of plus-strand RNA viruses (1,6,10,29,35). New viruses or strains may emerge via recombination between different viral RNAs or between viral and host RNAs (29,35).…”
mentioning
confidence: 99%